Repair or accommodation? Split antecedent ellipsis and the limits of repair. Issue 1 (11th July 2019) - Frazier, Lyn; Duff, John
Abstract : We begin from the assumption that the grammar requires syntactic matching between an elided verb phrase (VP) and its antecedent. When a fully matching antecedent cannot be found, the antecedent will be repaired if there is evidence for the repair, only a few operations are needed, and the repair reverses a natural speech error. This view correctly predicts that acceptability judgements are inversely correlated with the degree of difficulty of the repair (Arregui et al. 2006 ; Frazier 2013 ) and lower when a repair is required than when it is not (Kim & Runner 2018 ; Clifton et al. 2019 ), for example. Split antecedent ellipsis looks like a proto-typical case of repair since by definition no matching antecedent is available. It will be argued, however, that split antecedent ellipsis does not involve repair. The results of several experiments show that split antecedent ellipsis does not exhibit the hallmarks of repair. Rather it may involve ordinary accommodation. This raises the question of when the processor repairs an input and when it merely accommodates an antecedent of the appropriate type. We suggest that repair to a grammatical form is unavailable for split antecedent ellipsis because syntactic representation is only reliably available for the last independent clause.